Case report: Whole genome sequence of Clostridium perfringens JUM001 causing acute emphysematous cholecystitis - Tohya, Mari; Otsuka, Tomohiro; Yoshimoto, Jiro; Ishizaki, Yoichi; Kirikae, Teruo; Watanabe, Shin (Frontiers in Microbiology, 2022)
A strain of Clostridium perfringens was isolated from the bile sample of a patient with emphysematous cholecystitis who underwent a laparoscopic cholecystectomy, followed by treatment with meropenem and recovery. Metagenomic analysis of the bile sample showed that 99.73% of the bile microbiota consisted of C. perfringens JUM001, indicating that this strain was the causative pathogen of acute emphysematous cholecystitis in this patient. Complete genome sequencing showed that C. perfringens JUM001 contained a circular chromosome of 3,231,023 bp and two circular plasmids, pJUM001-1 of 49,289 bp and pJUM001-2 of 47,855 bp. JUM001 was found to possess a typing toxin gene, plc, but no other typing toxin genes, indicating that its toxinotype is type A. The plasmids pJUM001-1 and pJUM001-2 belonged to the pCP13-like and pCW3-like families of plasmids, respectively, which are characteristic conjugative and archetypical plasmids of C. perfringens. Phylogenetic analysis showed that JUM001 was closely related to C. perfringens strain JXNC-DD isolated from a dog in China. To our knowledge, this is the first report of whole-genome sequences of a clinical isolate of C. perfringens causing acute emphysematous cholecystitis.